Analyzing the BER and optical fiber length performances in OFDM RoF links - Marwa M. Kareem; Sameer A. S. Lafta; Hadi Fakhir Hashim; Raed Khalid Al-Azzawi; Adnan Hussein Ali (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Radio over fiber (RoF) can be assessed as a system of most convenient combination of optical fiber and radio signals. The technique of orthogonal frequency division multiplexing (OFDM) considers as a data distribution over a huge number of carriers having spaced from each other with specific frequencies at overlap bands. Hence incorporates OFDM with the optical fiber, OFDM-RoF system can be increased the modulation RF access capacity besides high-speed data transmission, it considers a broadband communication trend of the current and future applications specifically for 5G mobile. The optical network scenarios of various RF can be model with optisystem software, and OFDM in addition to use a section of the orthogonal multiplex frequency of 16-quadrature amplitude modulation (QAM) RF modulating signal. In the optical domain, Mach-Zehnder modulator (MZM) optical modulators are used to carry out different results with different fiber lengths. An OFDM-RoF wireless communication system considers as advanced data rate transmission achievement by minimum delays. The essential goal of this paper is for identifying the minimum bit error rate (BER) for the 16-QAM modulation with varying fiber length. The OFDM-RoF system can be able for realizing a fiber length 100 km with a restricted decreasing in the received power so that the constellation noise is became greater despite of applying electrical amplification and optical amplification.